2015
DOI: 10.1002/chin.201508090
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Gold‐Catalyzed Carbocyclization of Phenols with a Terminal Alkyne via an Intramolecular ipso‐Friedel—Crafts Alkenylation.

Abstract: A new method to synthesize spiro[4.5]cyclohexadienone derivatives with an exo‐cyclic olefin unit is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“… 355 Spiro[4.5]cyclohexadienones have been also obtained by a gold(I)-catalyzed carbocyclization of phenols with a terminal alkyne via intramolecular ipso -Friedel–Crafts. 356 Aryl alkynylphosphonates also undergo intramolecular gold(I)-catalyzed hydroarylation to give phosphacoumarins. 357 …”
Section: Hydroarylation and Hydroheteroarylation Of Alkynesmentioning
confidence: 99%
See 1 more Smart Citation
“… 355 Spiro[4.5]cyclohexadienones have been also obtained by a gold(I)-catalyzed carbocyclization of phenols with a terminal alkyne via intramolecular ipso -Friedel–Crafts. 356 Aryl alkynylphosphonates also undergo intramolecular gold(I)-catalyzed hydroarylation to give phosphacoumarins. 357 …”
Section: Hydroarylation and Hydroheteroarylation Of Alkynesmentioning
confidence: 99%
“…Aryl alkynoate esters 407 afford coumarin derivatives 408 in the presence of gold­(I) by intramolecular hydroarylation under anhydrous conditions (Scheme ). ,, It has been recently reported that the same substrates under the same reaction conditions swapping from anhydrous to wet solvent undergo a gold­(I)-catalyzed spirocyclization under mild conditions, giving spirolactones 409 in high yields . Spiro[4.5]­cyclohexadienones have been also obtained by a gold­(I)-catalyzed carbocyclization of phenols with a terminal alkyne via intramolecular ipso -Friedel–Crafts . Aryl alkynylphosphonates also undergo intramolecular gold­(I)-catalyzed hydroarylation to give phosphacoumarins …”
Section: Hydroarylation and Hydroheteroarylation Of Alkynesmentioning
confidence: 99%